Hermeneutics and Language in Purva Mimamsa: A study in Sabara Bhashya - Chethimattam, John B (Journal of Dharma, 1984)
Othmar Gächter Hermeneutics and Language in Purva Mimamsa A study in Sabara Bhashya, Delhi : Motilal Banarsidass, 1983, pp. x, 164, Rs. 100.00